2015
DOI: 10.5430/jha.v4n3p45
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reward system among health care workers performance: a case study of university of Calabar teaching hospital Calabar, Nigeria

Abstract: The study investigated the effect of reward system on health care workers performance in Teaching Hospital. It examined the relationship among monetary and non-monetary rewards and employees' performance in University of Calabar Teaching Hospital (UCTH). Desk survey was used in gathering relevant information. Primary sources were questionnaire, observation and interview, while secondary data were gathered from internet, textbooks, journals and libraries. Chi-square statistical tool was used and the findings re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A similar study among HWs in Lagos, Nigeria indicated the existence of a positive relationship between reward system and employee job performance, most especially where agreement reached with the workers' union on salary and incentives were implemented (Abosede & Adekunle, 2012). Nevertheless, contradicting findings were made in Calabar Teaching Hospital where it was revealed that monetary rewards had a positive impact on employees' performance while non-monetary rewards had a negative effect on employees' performance (James et al, 2015). Based on the findings from this study, the reward intervention undertaken by the Narok County health management has a role in motivating the health workforce, thus leading to improved healthcare system performance even though its application among the HWs is at a very low scale.…”
Section: Discussionmentioning
confidence: 44%
“…A similar study among HWs in Lagos, Nigeria indicated the existence of a positive relationship between reward system and employee job performance, most especially where agreement reached with the workers' union on salary and incentives were implemented (Abosede & Adekunle, 2012). Nevertheless, contradicting findings were made in Calabar Teaching Hospital where it was revealed that monetary rewards had a positive impact on employees' performance while non-monetary rewards had a negative effect on employees' performance (James et al, 2015). Based on the findings from this study, the reward intervention undertaken by the Narok County health management has a role in motivating the health workforce, thus leading to improved healthcare system performance even though its application among the HWs is at a very low scale.…”
Section: Discussionmentioning
confidence: 44%
“…There are other ways to reward employees beyond financial compensation. Some of these include recognition and praise from their superiors, providing opportunities for their development, and taking on meaningful projects [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A survey by James et al, (2015) on the reward system framework on healthcare professional productivity in Nigeria utilized a blending technique approach. The review population includes 277 workers.…”
Section: Empirical Review Employee Motivation and Organisational Perf...mentioning
confidence: 99%